Interplay between inter- and intraparticle interactions in bi-magnetic core/shell nanoparticles. Issue 24 (14th October 2021) - Omelyanchik, A.; Villa, S.; Vasilakaki, M.; Singh, G.; Ferretti, A. M.; Ponti, A.; Canepa, F.; Margaris, G.; Trohidou, K. N.; Peddis, D.
Abstract : This paper shed lights on the interplay among intra- and inter-particle interactions in different hard/soft bi-magnetic core/shell nanoarchitecture. Abstract : The synthesis strategy and magnetic characterisation of two systems consisting of nanoparticles with core/shell morphology are presented: an assembly of hard/soft nanoparticles with cores consisting of magnetically hard cobalt ferrite covered by a magnetically soft nickel ferrite shell, and the inverse system of almost the same size and shape. We have successfully designed these nanoparticle systems by gradually varying the magnetic anisotropy resulting in this way in the modulation of the magnetic dipolar interactions between particles. Both nanoparticle systems exhibit high saturation magnetisation and display superparamagnetic behaviour at room temperature. We have shown strong exchange coupling at the core/shell interface of these nanoparticles systems which was also confirmed by mesoscopic modelling. Our results demonstrate the possibility of modulating magnetic anisotropy not only by chemical composition but also by adopting the proper nano-architecture.